(untitled) (Research, Society and Development, 2020)
This paper explores the poetry within poems by Carlos Drummond de Andrade as a tool for science learning and is a an outcome of the association of Memorial Carlos Drummond de Andrade from Itabira-MG and the Grupo de Educação Tutorial Conexões de Saberes em Física e Popularização da Ciência. The work consisted on the interpretation and contextualization of the rich vocabulary of the poems and on the presentation of scientific experiments related to parts of the poems to an audience formed by students and teachers of schools in the city and region. The proposed work stimulated the students’ interaction and the comprehension the physical phenomena in a ludic way. The paper highlights the positive results regarding the interdisciplinarity between science and literature, the improvement of the perceived value of the local culture, as well as the teaching of experimental practice in a pleasant way for learning. These results reinforce the importance of Art and Physics as a language for cultural development.